Laparoscopic Management Of Pediatric Abdominal Surgical Emergencies At A Tertiary Care Centre - Bhojwani, Dev; Pattanshetti, Swapnil (Journal of Neonatal Surgery, 2025)
Background: Intestinal malrotation and its associated complications represent important causes of pediatric abdominal emergencies, particularly in the neonatal and early infancy period. Delay in diagnosis may result in volvulus, bowel ischemia, perforation, sepsis, and mortality. Objective: To analyze the clinical presentation, operative findings, management, and outcomes of pediatric patients presenting with malrotation and related intestinal pathologies in a tertiary care center. Methods: This case series includes ten pediatric patients ranging from 4 days to 16 years of age. Clinical data were reviewed with emphasis on age at presentation, presenting symptoms, intraoperative findings, surgical procedures performed, and postoperative outcomes. The primary surgical intervention for malrotation was Ladd’s procedure, with additional corrective procedures performed when indicated. Results: Neonates predominantly presented with bilious vomiting and feed intolerance, whereas older children presented with abdominal pain, distension, and features of obstruction. Midgut volvulus, duodenal atresia, congenital bands, and perforative peritonitis were observed intraoperatively. Ladd’s procedure was performed in all malrotation-associated cases. Eight patients recovered completely, one was discharged in stable condition at request, and one neonatal patient with gangrenous bowel and septic shock expired. Mortality was directly associated with delayed presentation and irreversible bowel ischemia. Conclusion: Early recognition and timely surgical intervention are critical determinants of outcome in pediatric malrotation. When treated before the development of bowel necrosis, prognosis is excellent..